2004
DOI: 10.1097/00130404-200411000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Toxicity from Craniospinal Irradiation

Abstract: Our proton-beam technique for craniospinal irradiation of pediatric medulloblastoma has successfully reduced normal-tissue doses and acute treatment-related sequelae. This technique may be especially advantageous in children with a history of myelosuppression, who might not other wise tolerate irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(30 citation statements)
references
References 25 publications
1
28
0
1
Order By: Relevance
“…Early reports of proton use shows that clinical responses can be achieved at a similar rate to photons. There are many small studies reporting reduced dosimetry to non-target tissues and even reduced incidence of secondary malignancy [28,29]. There is a robust experience using photon based radiation approaches in MB, and the long term outcome data for proton based therapy is just starting to mature.…”
Section: Interventional Proceduresmentioning
confidence: 99%
“…Early reports of proton use shows that clinical responses can be achieved at a similar rate to photons. There are many small studies reporting reduced dosimetry to non-target tissues and even reduced incidence of secondary malignancy [28,29]. There is a robust experience using photon based radiation approaches in MB, and the long term outcome data for proton based therapy is just starting to mature.…”
Section: Interventional Proceduresmentioning
confidence: 99%
“…In all subgroups of patients, surgery is first line treatment, which aims for maximal tumor resection. Postsurgical treatment is then varied with high-risk groups receiving higher-dose multimodal chemotherapy protocols in addition to craniospinal radiation (2, 3740). There are substantial concerns, however, over the long-term neurocognitive sequelae of whole brain radiation on the developing brain meaning that in patients younger than the age of 3 years (or sometimes as old as 7 years) craniospinal radiation is often delayed or eliminated (3, 3844).…”
Section: Therapeutic Targeting Of Medulloblastomasmentioning
confidence: 99%
“…Consequently, most radiation oncologists prefer to include the entire vertebral body and growth plate in the treatment volume for growing children and uniformly inhibit growth rather than risk inducing lordosis from radiation dose asymmetry anterior to posterior. Yuh, et al published early results on the treatment of three young patients treated with CSI with a single posteroanterior beam direction using three matched fields along the superior-inferior direction, with the beam stopping just beyond the thecal sac (8). The authors reported favorable early outcomes as minimal effects on blood counts were reported for these children and they experience less nausea, decreased appetite and odynophagia than would be expected for CSI.…”
Section: Introductionmentioning
confidence: 99%